ANALISIS FAKTOR KOMUNIKASI ONLINE DAN BRAND LOVE MANCHESTER UNITED SEBAGAI SPORTS BRAND PADA PENGGEMAR MANCHESTER UNITED DI BANDUNG - Christian Wibisono (Bina Ekonomi, 2018)
A brand for sport teams nowadays is a very valuable asset (Burrow, 2013). Sports team need to improve brand image like businesses do. These sports team conduct online communication to improve their brand image. Manchester United do this by managing their official Facebook, Twitter, Instagram and official website account. With so many factors to manage and monitor, the task of managing this online communication channel can be a very demanding task. The objective of this paper is to try to make it less complicated. From twenty indicators of online communication, using factor analysis, the result is five factors namely: twitter junkie, website user, IG and FB user, news hunter, and brand love.Keywords: brand love; sports marketing; online communication; factor analysis